23 things they don't tell you about capitalism - Chang, Ha-joon 1963- (Penguin Books, 2011)
In 23 Things They Don't Tell You About Capitalism the award-winning Ha-Joon Chang dispels the myths and prejudices that have come to dominate our understanding of how the world works. He succeeds in both setting the historical record straight ('the washing machine has changed the world more than the internet'; 'the US does not have the highest living standard in the world'; 'people in poor countries are more entrepreneurial than people in rich countries') and persuading us of the consequences of his analysis ('making rich people richer doesn't make the rest of us richer'; 'companies should not be run in the interest of their owners'; 'financial markets need to become less, not more, efficient')